PERANAN ORANG TUA DALAM MENDIDIK ANAK DI RUMAH DESA PULAU LAWAS KECAMATAN BANGKINANG KABUPATEN KAMPAR - Rizky Rahmadani; Tity Maemunaty; Said Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:This research is based on the less notice of the parents to children around age 6-12 years old in Lawas Island Village, Bangkinang subdistrict, Kampar regency. The aim of this research is about how is the parents role in educating their children at Lawas island, bangkinang subdistrict , Kampar regency. The purpose of this research is to determine the role of parents in educating their children at lawas, bangkinang subdistrict , Kampar regency.The population of this research are 143 participants an the sample of this research are 30 participants which is took by random sampling technique. The data collection instrument is by questionaire around 90 statements and after the trial there are 80 statements left that can be used for research instruments. The analysis data is quantitative descriptive . the result of this research is the role of parentsin educating their children at lawas island, bankinang subdistrict , kampar regency by recapitulation of presentation value, the result is high level by (SS-S) 82,9 % and (KD)11,1 % and (SR+P) 5 % with mean value 4.0 in high level .Keywords: Role, Parents, Educating